2010
DOI: 10.1007/978-3-642-14075-4_27
|View full text |Cite
|
Sign up to set email alerts
|

Haptic/VR Assessment Tool for Fine Motor Control

Abstract: Abstract. The Nine Hole Peg Test (NHPT) is routinely used in clinical environments to evaluate a patient's fine hand control. A physician measures the total time required to insert nine pegs into nine holes and obtains information on the dexterity of the patient. Even though this method is simple and known to be reliable, using a virtual environment with haptic feedback instead of the classical device could give a more complete diagnosis which would isolate different constituting components of a pathology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Grasping force is simultaneously recorded using three force sensors located inside the handle. The VPIT setup is described in more details in previous work [13], [17].…”
Section: B Apparatusmentioning
confidence: 99%
“…Grasping force is simultaneously recorded using three force sensors located inside the handle. The VPIT setup is described in more details in previous work [13], [17].…”
Section: B Apparatusmentioning
confidence: 99%
“…While tests have been recently designed using computercontrolled haptic interfaces [15,16], we believe that it is important that participants perform the real task with collocation of visual and haptic feedback. Participants may also prefer the appearance of the real object, and our experience of robot-assisted rehabilitation with stroke subjects has taught us the importance of this factor for the participants' motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Sveistrup (2004) observed that integration of appropriate haptic feedback in VR increases immersion and the sense of presence for users, which appears to contribute to improved training performance, particularly in difficult tasks. Additionally, haptic devices can be used to produce biomechanical and neuromuscular interactions in VR and to collect kinematic measures of patient functional and motor abilities (Bardorfer, Munih, Zupan, & Primozic, 2001; Emery, Samur, Lambercy, Bleuler, & Gassert, 2010).…”
Section: Directions Of Current Research and Seminal Studiesmentioning
confidence: 99%